2004
DOI: 10.1016/s1097-2765(04)00060-7
|View full text |Cite
|
Sign up to set email alerts
|

SUMO Promotes HDAC-Mediated Transcriptional Repression

Abstract: Recently, SUMO modification has been shown to impart repressive properties on several transcriptional regulatory proteins. Indeed, the ETS domain transcription factor Elk-1 is modified by SUMO, and this modification is reversed by ERK MAP kinase pathway activation. This causes a switch from a repressive to activated state. However, the mechanism(s) of SUMO-mediated transcriptional repression is unclear. Here, we have investigated how sumoylation of Elk-1 leads to transcriptional repression. We demonstrate that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
249
2
3

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 316 publications
(268 citation statements)
references
References 22 publications
14
249
2
3
Order By: Relevance
“…SUMO modification has been described to influence the assembly of transcription factors on promoters and the recruitment of chromatin-modifying enzymes. SUMOylation of Elk-1, for example, results in the recruitment of histone deacetylase activity, in particular HDAC-2, to promoters (Yang and Sharrocks, 2004). The N-terminal portion of NCoR interacts with HDAC3 and Sin3A (Heinzel et al, 1997;Guenther et al, 2000;Wen et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…SUMO modification has been described to influence the assembly of transcription factors on promoters and the recruitment of chromatin-modifying enzymes. SUMOylation of Elk-1, for example, results in the recruitment of histone deacetylase activity, in particular HDAC-2, to promoters (Yang and Sharrocks, 2004). The N-terminal portion of NCoR interacts with HDAC3 and Sin3A (Heinzel et al, 1997;Guenther et al, 2000;Wen et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…SUMOylation of N-CoR RDI or RDIII may thus very well play important roles in regulating the interaction with nuclear receptors. Several reports showed that class I (HDAC1, HDAC2) and class II HDACs (HDAC4, HDAC6) are targets for SUMO modification (David et al, 2002;Kirsh et al, 2002;Girdwood et al, 2003;Yang and Sharrocks, 2004). Interestingly, histones are also subject to SUMOylation and posttranslational modifications play important roles in the regulation of chromatin structure and function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, indirect routes by which MAPK cascades can cause localized nucleosomal modification at inducible genes -for example, by promoting association of histone acetyltransferases (HATs) with transcription factors in a phosphorylation-dependent manner (Mayr and Montminy, 2001;Yang et al, 2003) -have also emerged, linking localized histone acetylation with MAPK activation. A recently reported variation of this involves the interplay between MAPKregulated SUMOylation of the transcription factor Elk1 and its interaction with histone deacetylases (Yang and Sharrocks, 2004). Finally, recent evidence from yeast indicates a novel role for MAPKs as components of promoter-bound transcription complexes.…”
mentioning
confidence: 94%
“…Histone deacetylases (HDACs) are generally correlated with repression of transcription and can be recruited to sumoylated transcription factor complexes. For example, SUMO modification of the transcription factor Elk-1 has been correlated with increased association with HDAC2 [31]. Additionally, sumoylation of the co-activator p300 is associated with increased levels of HDAC6 [32].…”
Section: Sumoylation and Transcriptionmentioning
confidence: 99%